Queer youth, intoxication and queer drinking spaces. (16th March 2019) - Hunt, G.; Antin, T.; Sanders, E.; Sisneros, M.
ABSTRACT: Research on intoxicating substances and gender has developed considerably in the last 30 years, especially in the social sciences as feminist scholars highlighted the contradictory discourses about young women's intoxication. Nevertheless, there still remain significant gaps if we are to fully understand the role and meaning of intoxication for all young people and not merely for heterosexual, cisgender young people. As a way of exploring the possible limitations of this legacy, we will examine the qualitative data from 52 in-depth interviews with self-identified LGBTQ young people. Our analysis explores the relationships between meanings of intoxication and sexual and gender identities, drinking spaces, and the extent to which notions of masculinity and femininity influence alcohol consumption and drinking practices among LGBTQ youth. As gender expressions among young people, especially those who identify as LGBTQ, become increasingly nuanced and fluid, understanding the role of social and cultural practices of alcohol consumption in the performance of sexual and gender identities may increase our understanding of the ways in which sexuality and gender influence alcohol consumption.